2007
DOI: 10.1529/biophysj.106.101428
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolving Single-Molecule Intensity Distributions for Quantitative Microscopy Measurements

Abstract: In fluorescence microscopy, images often contain puncta in which the fluorescent molecules are spatially clustered. This article describes a method that uses single-molecule intensity distributions to deconvolve the number of fluorophores present in fluorescent puncta as a way to "count" protein number. This method requires a determination of the correct statistical relationship between the single-molecule and single-puncta intensity distributions. Once the correct relationship has been determined, basis histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 39 publications
10
90
0
Order By: Relevance
“…As suggested in Ref. 24, there might be other experimental factors that can lead to asymmetric intensity distributions.…”
Section: B1 Complete Intensity Distributionmentioning
confidence: 90%
“…As suggested in Ref. 24, there might be other experimental factors that can lead to asymmetric intensity distributions.…”
Section: B1 Complete Intensity Distributionmentioning
confidence: 90%
“…Note that single-molecule intensity distributions have an intrinsic asymmetry due to the influence of the detection probability. As suggested in (223) there might be other experimental factors that can lead to asymmetric intensity distributions.…”
Section: C5 Complete Intensity Distributionmentioning
confidence: 93%
“…5͑a͔͒ displayed a markedly different photon distribution and is well-approximated by a single Gaussian, as expected for a random noise source. Previous studies 30 showed that the intensity of a population of fluorescently tagged molecules, where each molecule is labeled with "n" fluorophores, is a smooth long-tailed distribution. It is therefore interesting to note that our data reflect a multipeak intensity distribution.…”
Section: Optical Visualization Of Dna Translocation Through a Solimentioning
confidence: 99%